Research methods - Jackson, Sherri L. (Thomson Wadsworth, 2008)
Sherri Jackson's RESEARCH METHODS: A MODULAR APPROACH combines a lively writing style with a novel approach to offer a refreshing alternative for the research methods course. Topics are treated in relatively compact units that, though logically sequenced, can be used in any order. The critical thinking theme that threads through the book engages your thinking by asking you to continually evaluate evidence. .Brief, yet comprehensive, this text will help you master the material in an engaging way